1976
DOI: 10.1073/pnas.73.4.1338
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy and hyperplasia of somatostatin-containing D-cells in diabetes.

Abstract: Insulin-, glucagon-, and somatostatin-containing cells, identified by immunofluorescent staining, were quantitated morphometrically in sections of pancreas obtained from diabetic and nondiabetic humans and rats. Both the volume density and number of somatostatin-and glucagon-containing cells were The other diabetic pancreas was obtained from a 31-yearold white female with a 29-year history of juvenile-type diabetes who died of renal insufficiency. Grossly, the pancreas was indurated and microscopic examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
120
1
4

Year Published

1977
1977
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(141 citation statements)
references
References 29 publications
16
120
1
4
Order By: Relevance
“…Administration of exogenous somatostatin inhibits the release of insulin and glucagon [8,9]. These observations, together with those of D cell hyperplasia and hypertrophy and of increased pancreatic somatostatin-like immunoreactivity in streptozotocin-and alloxaninduced diabetes in the rat [10][11][12] and in human insulin-dependent diabetes [13], suggest that somatostatin exhibits an important role in the physiology of islet function and possibly in the pathophys.-iology of diabetes.It has recently been reported that plasma somatostatin-like immunoreactivity is elevated in alloxan diabetic dogs [14] and in streptozotocin diabetic rats [15] and that somatostatin secretion from the isolated perfused pancreas of alloxan diabetic rats is exaggerated in response to arginine [16]. In another study, by contrast, normal pancreatic somatostatin responses to arginine, isoproterenol and calcium and a diminished response to glucose were seen in streptozotocin diabetic dogs [17].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Administration of exogenous somatostatin inhibits the release of insulin and glucagon [8,9]. These observations, together with those of D cell hyperplasia and hypertrophy and of increased pancreatic somatostatin-like immunoreactivity in streptozotocin-and alloxaninduced diabetes in the rat [10][11][12] and in human insulin-dependent diabetes [13], suggest that somatostatin exhibits an important role in the physiology of islet function and possibly in the pathophys.-iology of diabetes.It has recently been reported that plasma somatostatin-like immunoreactivity is elevated in alloxan diabetic dogs [14] and in streptozotocin diabetic rats [15] and that somatostatin secretion from the isolated perfused pancreas of alloxan diabetic rats is exaggerated in response to arginine [16]. In another study, by contrast, normal pancreatic somatostatin responses to arginine, isoproterenol and calcium and a diminished response to glucose were seen in streptozotocin diabetic dogs [17].…”
mentioning
confidence: 72%
“…Administration of exogenous somatostatin inhibits the release of insulin and glucagon [8,9]. These observations, together with those of D cell hyperplasia and hypertrophy and of increased pancreatic somatostatin-like immunoreactivity in streptozotocin-and alloxaninduced diabetes in the rat [10][11][12] and in human insulin-dependent diabetes [13], suggest that somatostatin exhibits an important role in the physiology of islet function and possibly in the pathophys.-iology of diabetes.…”
mentioning
confidence: 72%
“…On the other hand it is possible that SSTRs are upregulated as a defense mechanism against hyperglucagonemia. Previous studies demonstrated a hyperplasia and hypertrophy of pancreatic D-cells in type 1 and type 2 diabetes (Rahier et al, 1983;Orci et al, 1976;Iki and Pour 2007;Gomez Dumm et al, 1995). Thus, both the increase in SST production as well as SSTR Page 9 of 29 A c c e p t e d M a n u s c r i p t 9 expression on A-cells could provide a defense mechanism against hyperglucagonemia; however, experimental evidence supporting this hypothesis remains to be established.…”
Section: Rodentsmentioning
confidence: 96%
“…Treatment with insulin normalized the elevated basal plasma SST levels in these patients (Segers et al, 1989). Animals with streptozotocin-induced diabetes and NOD mice with autoimmune diabetes have increased size and number of D-cells as well as increased pancreatic SST content (Orci et al, 1976;Gomez Dumm et al, 1995;Kanatsuka et al, 1981).…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 97%
See 1 more Smart Citation